2017
DOI: 10.1590/0100-29452017012
|View full text |Cite
|
Sign up to set email alerts
|

MORPHOANATOMY OF Garcinia madruno (KUNTH) HAMMEL (CLUSIACEAE) UNDER WATERLOGGED CONDITIONS

Abstract: -Garcinia madruno (Kunth) Hammel is a neotropical tree that naturally occurs in terra firme forests and is important as a source of income and medicine for Amazonian populations. This study describes and compares the morphoanatomical responses of plants under conditions of stress and normoxia. Young plants of Garcinia madruno were subjected to two water regimes: daily controlled irrigation and waterlogged for 84 days. Hypertrophic lenticels, adventitious roots and anatomical characteristics of the roots and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…The presence of cuticles attests to the interaction between plants and the environment. A previous study by Abreu et al (2017) found thick cuticle wax on G. madruno under flooded conditions. They pointed out that this condition led to low water potential (Medri et al, 2011); thus, thick wax offered more protection to G. madruno (Abreu et al, 2017).…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…The presence of cuticles attests to the interaction between plants and the environment. A previous study by Abreu et al (2017) found thick cuticle wax on G. madruno under flooded conditions. They pointed out that this condition led to low water potential (Medri et al, 2011); thus, thick wax offered more protection to G. madruno (Abreu et al, 2017).…”
Section: Resultsmentioning
confidence: 78%
“…The types of epidermal cells which are straight, undulated, and sinuate observed in the Tomovita species can be utilised in the phylogenetic study of morphological features and determination of linkages across species (Gahagen, 2015). In Garcinia cases, epidermal cells of G. dulcis (Begum, 2020) and G. madruno (Abreu, 2017) showed sinuosity, while G. cambogia exhibited undulating to irregular cells (Sreelakshmi et al, 2014). An epidermal anticlinal wall pattern can be a suitable anatomical feature for species delimitation in Garcinia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tipe tangkai daun yang mencirikan tingkatan marga ditemukan pada G. dioica, C. sumatranum, B. glauca, A. complanata, dan S. benzoides. Marga Garcinia memiliki bentuk berkas pengangkut tangkai daun yang umumnya berbentuk busur menekuk (Pathirana & Herat 2004;Abreu et al 2017;Priya & Hari 2018). Bentuk berkas pengangkut C. sumatranum adalah busur dengan ujung menekuk.…”
Section: Tangkai Daununclassified